2022
DOI: 10.1186/s12889-022-13154-4
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial issues and sleep quality among seafarers: a mixed methods study

Abstract: Background Seafarers, especially those working for a prolonged period of time, are exposed to a high number of social, psychological and physical stressors including irregular working hours. Aim This study aims to identify important aspects of Asian seafarers’ psychosocial wellbeing and quality of sleep that could affect safety and health of the seafarers in long voyage tankers. Methods In this mixed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The previously mentioned sleep problems indicate an increase in the workload of seafarers due to various factors, such as economic or safety factors, and this leads to a decrease in free time and the amount of sleep. Baygi et al 21 state that the quality of sleep was mentioned as the most significant health problem they had to deal with on board, and consequently, various difficulties arise, such as physical and mental difficulties that affect the functioning of seafarers, which poses a danger to health, but also to safety at sea. The results of our study on a convenient sample of seafarers suggest that almost 40% of our sample reported having sleep difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously mentioned sleep problems indicate an increase in the workload of seafarers due to various factors, such as economic or safety factors, and this leads to a decrease in free time and the amount of sleep. Baygi et al 21 state that the quality of sleep was mentioned as the most significant health problem they had to deal with on board, and consequently, various difficulties arise, such as physical and mental difficulties that affect the functioning of seafarers, which poses a danger to health, but also to safety at sea. The results of our study on a convenient sample of seafarers suggest that almost 40% of our sample reported having sleep difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that because of this, seafarers have difficulties with the quality of sleep, but also with the amount of sleep, which according to research should be an average of 7 h for adults. 20 Recent mixed methods study 21 indicated on sleeping problems as one of the essential threat to psychological well-being on-board. According to this study, on-board sleeping problems arise directly from working environment and working conditions.…”
Section: Introductionmentioning
confidence: 99%